Analysis Of Costing Variables In Decision Making Case Studies In Confectionery Companies (Msmes) - Amalia, Elma; Sundarta, M. Imam; Bimo, Widhi Ariyo (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2022)
The pandemic covid19 has caused MSME in Indonesia to experience a decrease in profit levels and cannot use capacity to the fullest, so there is capacity that can still be utilized by receiving special orders. Then this study aims to know how MSME apply the cost of goods manufacture by variabel costing method which can increase profits during the pandemi of Covid19 and how the MSME apply cost analysis by variabel costing in short term decision making. This research was conducted in Uniform Original Confection using quantitative data types which were then analyzed using descriptive methods.. Sample data collacted through interviews and observation regarding production data and cost incurred during the pandemi of Covid19 and when there of special orders. Sample data was determined using a purposive sampling technic and the samping technic used was a non probability sampling tehnic. The result of this studi this can be see through the total variabel production costs to produce 2.060 unit uniforms is Rp 65.685.160 then the variabel cost each unit is Rp 31.886, so MSME can do application and calculate cost of goods manucfature by variabel costing method consitently because thia method can generate profit for MSME. And the resultf of cost analysis by variabel costing method in short-term decision making, the company can receive the special order because with the special order the net profit obtained has increased by Rp 2.489.900.